2016
DOI: 10.5121/ijcsit.2016.8203
|View full text |Cite
|
Sign up to set email alerts
|

Examine Website Quality on M-Banking Services Adoption in Bangladesh

Abstract: Mobile banking allows consumers to operate their banking activities through their mobile device, tab, notepad, etc. Now a day's m-banking service is considered one of the easiest and convenient ways for any kind of financial transaction. More ever, in the Bangladesh popularity of m-banking service increased day by day. But very few research conducted user acceptance of m-banking service in Bangladesh, especially the impact of web side quality on customer acceptance preference. For that reason, we proposed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 80 publications
(122 reference statements)
0
5
0
Order By: Relevance
“…For this reason, the UTAUT2 model, as outlined in Figure 1 was chosen in this study to assess the relevance and effect of five moderator variables (age, gender, level of education, location of citizen's residence, and vernacular language options on e-government websites) on citizens' behavioral intention to adopt e-government services. Furthermore, the UTAUT2 is the most comprehensive model (Tavares, and Oliveira, 2016;Mahfuz, Khanam, and Hu, 2016) that has been extensively used in many contemporary empirical studies on ICT adoption and utilization (Al-Mamary, Alnashmi, Hassan and Shamsuddin, 2016; Venkatesh and Bala, 2008) -hence the same reason for the researchers to adopt it in this study. Moreover, in the context of the SADC region, specifically focusing on the Zimbabwean and Zambian case, the researcher found that empirical research on egovernment adoption and utilization using the UTAUT2 model are lacking (with the exception of Bwalya and Healy, 2010).…”
Section: Utaut2 Model Of E-government Adoptionmentioning
confidence: 99%
“…For this reason, the UTAUT2 model, as outlined in Figure 1 was chosen in this study to assess the relevance and effect of five moderator variables (age, gender, level of education, location of citizen's residence, and vernacular language options on e-government websites) on citizens' behavioral intention to adopt e-government services. Furthermore, the UTAUT2 is the most comprehensive model (Tavares, and Oliveira, 2016;Mahfuz, Khanam, and Hu, 2016) that has been extensively used in many contemporary empirical studies on ICT adoption and utilization (Al-Mamary, Alnashmi, Hassan and Shamsuddin, 2016; Venkatesh and Bala, 2008) -hence the same reason for the researchers to adopt it in this study. Moreover, in the context of the SADC region, specifically focusing on the Zimbabwean and Zambian case, the researcher found that empirical research on egovernment adoption and utilization using the UTAUT2 model are lacking (with the exception of Bwalya and Healy, 2010).…”
Section: Utaut2 Model Of E-government Adoptionmentioning
confidence: 99%
“…However, studies conducted by Owusu Kwateng et al (2019) and Merhi et al (2019) reported that SI is insignificant in determining users' BI to adopt m-banking services. On the contrary, multiple studies have highlighted the significance of SI on BI to adopt m-banking technologies (Mahfuz et al, 2016;Farzin et al, 2021;Chen et al, 2021;Penney et al, 2021;Thaker et al, 2021). Considering the aforementioned differences in opinion, this study proposes the following hypothesis:…”
Section: Social Influence (Si)mentioning
confidence: 92%
“…In addition, Owusu Kwateng et al (2019) validated EE as a strong precursor of BI to adopt m-banking services in their study conducted in Ghana. However, Mahfuz et al (2016) report contradictory results in the context of Bangladesh. Given this scenario, the present study anticipated a significant and positive effect of EE on BI:…”
Section: Effort Expectancy (Ee)mentioning
confidence: 97%
See 1 more Smart Citation
“…Regarding the relevant indices [9,10,[12][13][14][15][16], and according to IPA analysis, if the service item belongs to Quadrant I (Keep Up the Good Work), it means that consumers' expectation and satisfaction for this service is high, and the operator of this service item should 「 keep up the good work」in future management; if the service item belongs to Quadrant II (Possible Overkill), it means that consumers' expectation for this service is low but their satisfaction is high. This service item can meet the demands of consumers, but「over-supplied」, the operator should make adjustments according to the situation in future management; if the service item belongs to Quadrant III (Low Priority), it means that consumers' expectation and satisfaction for this service is low, and operators may give 「 low priority」to this service item during management improvement; If the service item belongs to Quadrant IV (Concentrate Here), it means that the consumers' expectation for this service is high, but satisfaction is low, and operatorsshould「strengthen the improvement of」this service item immediately; Figure 1.…”
Section: Important-performance Analysismentioning
confidence: 99%